Ethnic Identity through Character Construction: Examining Semantic Essence of Yoruba Names in Femi Adebayo’s Jagun Jagun and Bode Sowande’s Arede Owo - Kareeem Kolawole Ganiyu; Babatunde Covenant Olugbenga; Emmanuel Godwin Kalu (Britain International for Academic Research (BIAR-Publisher), 2025)
This study looks into the significance of thematic nomenclature in character construction within the rich cultural lineage of the Yoruba tradition, as depicted in the film